Uji UJI EFEKTIVITAS GEL EKSTRAK ETANOL 70% GETAH GAMBIR (Uncaria gambir. Roxb) dan BETADINE TERHADAP LUKA SAYAT PADA TIKUS PUTIH JANTAN (Rattus norvegicus) GALUR - sulasmi sulasmi (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2022)
Gambir (Uncaria gambir. Roxb) contains flavonoids, tannins, saponins and alkaloids that can help heal wounds. One of the main ingredients that gambir contains is catechins . Catechins are flavonoid compounds with anti-inflammatory, antioxidant and antibacterial properties derived from Gambir. This study aimed to compare wound healing time between ethanolic extracts of 70% gambir resin gel (Uncaria gambir. Roxb) with betadin preparations in male Sprague dawley rats (Rattus norvegicus). A total of 9 white rats (Rattus norvegicus) strain Sprague dawley were divided into 3 groups, a negative control group for gel base treatment and a positive control group for gambir sap gel preparations (Uncaria gambir. Roxb) betadine comparison group. This study was conducted by experimental method with a post-trial controlled group design. Each group is colored with group preparations, the treatment is carried out 3 × 1 every day. Wound healing time was analyzed by a one-way Anova test on spss. Healing ingroup I was 10.6 days, in group II, 10.3 days in group III and 9.3 days.